2007
DOI: 10.1002/rob.20226
|View full text |Cite
|
Sign up to set email alerts
|

Supporting wilderness search and rescue using a camera‐equipped mini UAV

Abstract: Wilderness Search and Rescue ͑WiSAR͒ entails searching over large regions in often rugged remote areas. Because of the large regions and potentially limited mobility of ground searchers, WiSAR is an ideal application for using small ͑human-packable͒ unmanned aerial vehicles ͑UAVs͒ to provide aerial imagery of the search region. This paper presents a brief analysis of the WiSAR problem with emphasis on practical aspects of visual-based aerial search. As part of this analysis, we present and analyze a generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
171
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(171 citation statements)
references
References 32 publications
0
171
0
Order By: Relevance
“…Practical implementation of search algorithms has been demonstrated in the wilderness search and rescue domain. Goodrich et al (2008) provided an extensive experimental analysis of UAV-enabled search with vision, which includes field trials with search and rescue operators. They utilized a small and light fixed wing UAV equipped with autopilot, GPS, and a video camera on a gimbal mount.…”
Section: Implementation and Field Resultsmentioning
confidence: 99%
“…Practical implementation of search algorithms has been demonstrated in the wilderness search and rescue domain. Goodrich et al (2008) provided an extensive experimental analysis of UAV-enabled search with vision, which includes field trials with search and rescue operators. They utilized a small and light fixed wing UAV equipped with autopilot, GPS, and a video camera on a gimbal mount.…”
Section: Implementation and Field Resultsmentioning
confidence: 99%
“…Research has shown that UASs could potentially be used to facilitate this work. Goodrich et al tested the effectiveness of these types of operations [1]. A key outcome of these field tests is the speculation that effectiveness could be enhanced if the roles of the UAV operator and video operator were combined.…”
Section: Related Workmentioning
confidence: 99%
“…Most existing Unmanned Aerial Systems (UASs) require two or more human operators [1,2]. Standard UAS practice is to have one human to control the aerial vehicle and another to control the camera or other payloads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban search and rescue (USAR) has been the most studied form of SAR in the robotics research community (Birk and Carpin, 2006;Gage et al, 2004;Poppinga et al, 2008;Murphy and Stover, 2008;Micire, 2008;Arai et al, 2008) and has become familiar as recent natural and man-made disasters have made the news the world over. On the opposite end of the spectrum, wilderness search and rescue (WiSAR) often involves only few victims with a large geographic search region (Goodrich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%